Comparison of the number and reasons for self-perceived barriers to accessing primary health care services between Roma and ethnic Albanians - Naum, Alvi (Zdravstveno varstvo, 2026)
Introduction To compare the number and reasons for self-perceived barriers to accessing primary health care (PHC) services between Roma/Egyptian and ethnic Albanians. Methods 533 adults (mean age: 45±18 years; ?60% women) reporting barriers to accessing PHC services were recruited consecutively during a nationwide survey in October 2024 across all four regions of Albania, using probability-proportional-to-size sampling. A semi-structured questionnaire was administered by trained interviewers inquiring about the number and reasons for self-perceived barriers to accessing PHC services, health characteristics, and sociodemographic factors. General linear models and binary logistic regression were employed to assess the association between perceived barriers and ethnic groups. Results 444 (?83%) participants were ethnic Albanians, whereas the remaining 89 (?17%) individuals belonged to other ethnic groups, including Roma (n = 57), Egyptians (n = 30), and Gorani or Macedonians (n = 2). Overall, cost and waiting time were the most common barriers. Roma/Egyptian minorities faced more cultural and language issues, whereas Albanians reported higher distrust and service-related expectations. The crude mean number of barriers to accessing PHC services was higher among Roma/Egyptian minorities than among Albanians (1.8 vs. 1.6, respectively; P = 0.04). The multivariable-adjusted odds of reporting ? 2 barriers to accessing PHC services were 93% higher among Roma/Egyptian minorities than in Albanians (P = 0.03). Conclusions Roma/Egyptian minorities experience more barriers in accessing PHC services than ethnic Albanians. However, the cost of services constitutes the main barrier across both groups. Conversely, communication-related barriers affect mainly Roma/Egyptian minorities, whereas Albanians perceive more systemic barriers. In Albania, there is a need for targeted, equity-focused interventions.
Keywords: access to health services; Albania; Albanija; barriers; dostop do zdravstvenih storitev; ethnic differences; etične razlike; manjšine Romov in Egipčanov; ovire; primarne zdravstvene storitve; primary health care; Roma and Egyptian minorities